2015
DOI: 10.3803/enm.2015.30.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Metformin-Associated Lactic Acidosis: Predisposing Factors and Outcome

Abstract: BackgroundMetformin is considered the first choice oral treatment for type 2 diabetes patients in the absence of contraindications. Rarely, life-threatening complications associated with metformin treatment are seen in some patients with underlying diseases. The aim of this study was to further investigate the clinical profiles and risk factors for metformin-associated lactic acidosis (MALA) and the treatment modalities according to survival.MethodsTo identify MALA, we performed a retrospective study in seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 18 publications
(19 reference statements)
1
25
0
2
Order By: Relevance
“…Other studies have also shown that metformin concentrations remain in a therapeutic range in mildly to moderately renal impaired patients [40]. At the same time, growing evidence suggests that the underlying disease associated with the tissue hypoxia rather than metformin use is related to lactic acidosis in diabetes [41][42][43]. In the present research, no case of lactic acidosis was observed during hospitalization for both groups.…”
Section: Discussionsupporting
confidence: 60%
“…Other studies have also shown that metformin concentrations remain in a therapeutic range in mildly to moderately renal impaired patients [40]. At the same time, growing evidence suggests that the underlying disease associated with the tissue hypoxia rather than metformin use is related to lactic acidosis in diabetes [41][42][43]. In the present research, no case of lactic acidosis was observed during hospitalization for both groups.…”
Section: Discussionsupporting
confidence: 60%
“…Owing to the multiple and often nonspecific signs and symptoms of MALA, as well as the potential impact of other conditions and medications that can predispose a patient to lactic acidosis, MALA can be difficult to predict or diagnose [21][22][23]. This is true especially in the absence of knowing the circulating metformin concentration in a patient presenting with symptoms [24]. However, it is known that MALA occurs when there is an imbalance between increased lactate production and impaired metabolism/reduced clearance.…”
Section: Risk Factors For Malamentioning
confidence: 99%
“…In addition, a majority of the patients reported have comorbidities that could contribute to hyperlactatemia. Renal impairment is the most common comorbidity reported in cases of MALA [5,10,18,25,[42][43][44]]. This has led to significant research regarding the safety of metformin use in patients with chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%